Dinamika Konflik Sosial dalam Penertiban Pedagang Kaki Lima di Kawasan Perkotaan - Cece Cece (JURNAL RISET MANAJEMEN (JURMA), 2026)
The presence of street vendors in urban areas is a social phenomenon that is inseparable from the economic dynamics of urban communities. On the one hand, street vendors provide an alternative source of livelihood for people in the informal sector; on the other hand, their presence is often seen as disrupting public order, urban aesthetics, and the function of public spaces. This situation gives rise to social conflict between local governments—as the authorities responsible for urban planning—and street vendors who are defending their economic space. This study aims to analyze the dynamics of social conflict in the process of regulating street vendors in urban areas and to identify the factors influencing the emergence of public resistance to regulation policies. The study employs a qualitative approach using descriptive methods. Data were collected through observation, interviews, and document analysis. The research findings indicate that social conflicts arising from street vendor regulation are influenced by conflicting interests between the government and vendors, poor policy communication, limited relocation space, and economic factors affecting urban communities. Repressive enforcement measures tend to provoke social resistance, whereas dialogic and participatory approaches are more effective in reducing conflict. This study emphasizes that the management of street vendors cannot be understood solely as a matter of urban order, but also involves aspects of social justice and the community’s right to sustain their economic livelihoods.